LAND STRUCTURAL CHANGES AND DEVELOPMENT OF VEGETABLE PRODUCERS IN BULGARIA - Teodora STOEVA; Violeta DIRIMANOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Land structural changes and development of small farmers are public phenomena arising on the basis of land use as an indispensable mean of production in the agricultural sector. After the transition from one political ideology to another, which lasted more than three decades, more than 10 years were necessary for the Bulgarian government to complete the land reform. The value of the gross agricultural output had declined during the last years. The national policy in most countries maintains agricultural consultancy organizations that aim to offer additional assistance services to small-scale farmers. The legislation should set out the objectives and scope of the consultancy activity, focusing on the way of development of rural areas. The relation between research activity should be regarded as the basis for the development and implementation of agricultural programs. The purpose of this article is to present and analyze the structural changes of land use for small-scale farming and development of the vegetable producers in Bulgaria. A number of contemporary scientific quantitative and qualitative methods are used to achieve the intended objective set in this study: systematic and comparative analysis, monographic analysis and expert assessment. The methodical framework of this article provides a summary overview of the main changes in the agricultural policy and the structure of land relations in Bulgaria. The processes in land relations, as public relations, are dominated by the changes in the institutional environment and socio-cultural traditions. The paper also has a narrow focus on achieving the key goal of presenting the links between land structural changes and their impact on the development of vegetable producers in Bulgaria. The results pointed out the fragmentation of the use of agricultural land, and the existence of a large number of small farms. For the research, we used data of the Ministry of Agriculture, Food and Forestry. The main conclusions are related to the land productivity in Bulgaria regarding field vegetable production is low despite the favourable soil and climatic conditions typical of the area. The structural changes present that the land used is mainly concentrated among small producers who are mainly vegetable producers. The large number of small-scale agricultural farmers is typical for Bulgaria and the main reason for this is the land reform carried out in the 1990s, when the land was returned in real borders to its owners and their heirs.